Analisis Sumber Modal Dan Penggunaan Modal Kerja Pada PT. Bank Negara Indonesia (Persero) Tbk - Desvriani, Ike; Valianti, Reva Maria; Lilianti, Emma (Universitas PGRI Palembang, 2023)
ABSTRACT Source of capital and usage of working capital determine efficacy of company of banking. Assessment of working capital in principle cause : total [of] asset, fluent obligation, and rotation of working capitalTarget of this research is to know how applying of analysis of[is source of capital and usage of working capital [at] PT. Bank Negara Indonesia ( Persero), Tbk.Method Analysis the used [is] quantitative descriptive analysis method by using ratio sufficiency of working capital which consist of three ratio type that is total ratio [of] asset to net working capital, fluent obligation ratio to net working capital and rotation of working capital. Source of capital and usage of annual report working capital of PT. Bank Negara Indonesia ( Persero) TbkThe result of research indicate that the source of capital and usage of year working capital 2016 to 2018 every year natural [of] improvement, year 2016 equal to 27.732.328 ,- year 2017 equal to 32.677.527 ,- and year 2018 equal to 37.572.183. role of capital source and usage of working capital of menunjukan mount effectiveness and efficient so that monetary rotation [of] banking can walk better. Analyse evaluation sufficiency of rate of change working capital of likuiditas. Total [of] asset of menunjukan 1.422, fluent obligation [of] menunjukan 95.280, and rotation of working capital of menunjukan 1.143 Keywords : Working Capital, Source Of Capital And Usage Of Working CapitalFundsThird Party. ABSTRAK Sumber modal dan penggunaan modal kerja menentukan keberhasilan perusahaan perbankan. Penilaian modal kerja pada prinsipnya menyebabkan : total aktiva, kewajiban lancar, dan perputaran modal kerja. Tujuan penelitian ini adalah untuk mengetahui bagaimana penerapan analisis sumber modal dan penggunaan modal kerja pada PT. Bank Negara Indonesia (Persero), Tbk.Metode analisis yang digunakan adalah metode analisis deskriptif kuantitatif dengan menggunakan rasio kecukupan modal kerja yang terdiri dari tiga jenis rasio yaitu rasio total aktiva terhadap modal kerja bersih, rasio kewajiban lancar terhadap modal kerja bersih dan perputaran modal kerja. Sumber modal dan penggunaan modal kerja laporan tahunan dari PT. Bank Negara Indonesia (Persero) Tbk. Hasil penelitian menunjukkan bahwa sumber modal dan penggunaan modal kerja tahun 2016 s/d 2018 setiap tahun nya mengalami peningkatan, tahun 2016 sebesar 27.732.328 ,- tahun 2017 sebesar 32.677.527 ,- dan tahun 2018 sebesar 37.572.183. peran sumber modal dan penggunaan modal kerja menunjukan tingkat efektivitas dan efisien sehingga perputaran keuangan perbankan dapat berjalan dengan baik. Analisis evaluasi kecukupan modal kerja tingkat perubahan likuiditas. Total asset menunjukan 1.422, kewajiban lancar menunjukan 95.280, dan perputaran modal kerja menunjukan 1.143. Keywords : Modal Kerja, Sumber Modal Dan Penggunaan Modal KerjaDana Pihak Ketiga.